Adolescents' and Parents' Attitudes Toward Adolescent Clinical Trial Participation: Changes Over One Year. (October 2018) - Tsevat, Rebecca K.; Radecki Breitkopf, Carmen; Landers, Sara E.; de Roche, Ariel M.; Mauro, Christine; Ipp, Lisa S.; Catallozzi, Marina; Rosenthal, Susan L.
Little is known about how adolescents' and parents' thoughts about participation in clinical trials change over time. In this study, adolescent (14-17 years)–parent dyads were asked about willingness to participate in a hypothetical reproductive health study. A year later, they were asked how their thoughts about the study had changed. Qualitative responses were coded and analyzed using framework analysis. Thirty-two percent of adolescents and 18% of parents reported changes in thoughts; reasons included general changes in perception, clearer understanding, new knowledge or experiences, increased maturity/age of adolescents, and changes in participants independent of the study. Adolescents and parents may benefit from learning about studies multiple times, and investigators should account for development and new experiences to optimize adolescent research enrollment.